Shaping the techno-social landscape of corrections: How values, technology, and culture influence the design of correctional service delivery applications - Ross, Stuart (Journal of criminology, 2024)
Over the past decade, a variety of digital platforms have emerged to deliver core correctional services. Understanding the challenges and drivers of correctional agencies’ digitalisation helps us to understand the processes that shape these technologies and their impact on correctional environments and practices. To bridge this gap, we conducted interviews with 26 software developers and other stakeholders involved in the digitalisation of corrections, aiming to explore the challenges encountered in designing and implementing digital service delivery technologies for correctional services. Our findings shed light on some key challenges faced by software developers and other stakeholders involved in the design process, including institutional culture, justice system bureaucracy, and public perceptions. These challenges significantly influence design processes and the availability of digital products for end users. They shape the techno-social landscape of correctional agencies and contribute to the dominance or absence of certain digital platforms or artefacts.